The Impact of Problem-Based Learning Model Assisted by Mentimeter Media in Science Learning on Students’ Critical Thinking and Collaboration Skills - Anggriani, Mitha Dwi; Haryanto, Haryanto; Atmojo, Setyo Eko (Universitas Pendidikan Ganesha, 2022)
This research is motivated by the ability of students who are still lacking to identify, understand, state, find solutions, and draw conclusions to the problems. In addition, students also tend to be passive in learning. This study aims to analyze the effect of the problem-based learning model with the aid of the mentometer on elementary school teacher education students' critical thinking and collaboration skills. The method used in this study is a quasi-experimental design with a non-equivalent control group. Critical thinking skills were collected with critical thinking skills tests in the form of essay tests and observation sheets to determine collaboration skills. The results show significant differences in critical thinking and collaboration skills between students who study using problem-based learning with the aid of a mentimeter and students who learn without using problem-based learning with the aid of a mentimeter. So, it can be concluded that the problem-based learning model assisted by a mentimeter influences elementary school teacher education students' critical thinking and collaboration skills.